ANALYSIS OF BULLYING IN UMSU PGSD STUDENTS - Amelia, Chairunnisa; Amanda, Silvia; Sari Sitepu, Melyani (Proceeding International Seminar of Islamic Studies, 2023)
Lack of knowledge is one of the factors that causes individuals to commit violence, namely bullying. Bullying is a repeated negative behavior that intends to cause displeasure or hurt by another person, either one or several people, directly against someone who is unable to fight it. According to Yahya and Ahmad (2005) in (Nathania et al., 2022) on a 2004 survey conducted by the Japanese Ministry of Education, it was stated that there were 24,898 cases of bullying of these cases occurring in private universities (PTS). The purpose of this literature review is to analyze the results of research analysis related to the level of knowledge of PGSD students at Muhammadiyah University of North Sumatra about bullying behavior. The research method used is a quantitative method.